(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
A sun-synchronous orbit, sometimes called an helio-synchronous orbit, is when the Earth orbits the sun at a constant angle relative to the Earth-sun direction. In this work, the analytical technique for third body perturbation on sun-synchronous orbit satellites for prograde and retrograde orbits computed for short periods At a time interval of one day, the dynamic development of sun-synchronous orbits is considered. It was accomplished by utilizing the numerical output results from the celestial mechanics’ version 1 software program package. The integration was carried out by using the Celestial Mechanics software program SATORB module (Beutler, 2005) created at the University of Bern’s Institute of Astronomy. With input data given by the Two-Line Elements (TLE). Represented by six orbital elements and three Coordinates axes and acceleration components which were used to solve the variation of parameters equations (VOP) using a technique known as collocation method. It is reasonable to assume that the change in orbital elements is seen in both types of perturbations that have the greatest impact on the moon’s impact. With the addition of the Geocentric equatorial coordinate system, Kepler’s orbit, and acceleration combinations, there was no discernible change in the coordinate system or acceleration components, which appeared to be secular in both results. The results show that the Moon perturbation has the greatest influence on orbital elements and that the perturbation is amplified by satellite heights.